Analysis Of Corruption Committed Jointly In Decision No. 163 PK / PID.SUS/2019 - Nasir Sitompul, Mhd.; Aisyah, Aisyah (International Asia Of Law and Money Laundering, 2026)
This study analyzes the application of the concept of inclusion (medeplegen) in corruption based on the Supreme Court Decision No. 163 PK/Pid.Sus/2019 which involves criminal disparities between actors who commit acts jointly. Using normative juridical methods with a qualitative approach, this study examines primary legal materials in the form of legislation and court decisions, as well as secondary legal materials from scientific journals and legal literature. The results showed that the criminal disparity was caused by differences in the qualification of the charges, the judge's perception of the role of the perpetrator, and the timing of the verdict. The Supreme Court granted judicial review by equalizing the crimes of the two perpetrators to bring about substantive justice based on the principle of gelyikwaardigheid. The juridical implications of this ruling create a precedent for the importance of consistency of judges in imposing criminal penalties on inclusion perpetrators, provide a signal to law enforcement to be careful in qualifying actions, and strengthen public confidence in the justice system in combating corruption.